2020
DOI: 10.1186/s13041-020-00606-4
|View full text |Cite
|
Sign up to set email alerts
|

Altered behavior in mice overexpressing soluble ST2

Abstract: Psychoneuroimmunological studies have clearly demonstrated that both cellular and humoral immunity are related to major depression. Soluble ST2 is regarded as a key molecule regulating immune system as well as cell proliferation. Indeed, soluble ST2 is reported to reduce IL-33-induced IL-6 and TNF-α production in macrophages and IL-33-induced IL-5 and IL-13 production in type 2 innate lymphoid cells. Elevated serum concentrations of soluble ST2 have been reported in patients with neuropsychiatric disorders, su… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 39 publications
0
11
0
Order By: Relevance
“…As noted above, sST2 is the soluble receptor of IL-33, and it is a key molecule for the immune system too. One researcher revealed that sST2 overexpression in mice resulted in decreased social interaction [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…As noted above, sST2 is the soluble receptor of IL-33, and it is a key molecule for the immune system too. One researcher revealed that sST2 overexpression in mice resulted in decreased social interaction [ 42 ].…”
Section: Discussionmentioning
confidence: 99%
“…Limited studies have reported the association between sST2 and depression. Kikuchi and colleagues established an animal model, and found that sST2 overexpression may reduce social behavior and enhance depressive‐like behavior by changing the composition of gut microbiota [34]. Another study conducted in 349 type 2 diabetes mellitus (T2DM) and non‐T2DM men with asymptomatic stage B heart failure (HF) indicated that T2DM HF patients had higher circulating levels of sST2 and had more somatic/affective depressive symptoms [14].…”
Section: Discussionmentioning
confidence: 99%
“…1. Before beginning testing, each mouse was observed in a clean cage for a general health check and neurological screening tests according to methods of our previous reports [28,[38][39][40]. The neurological screening tests were designed to detect any gross abnormalities in physical function.…”
Section: Behavioral Testmentioning
confidence: 99%